The Impact of Financial Inclusion on CO2 Emissions: The Mediating Role of Renewable Energy and the Moderating Role of Institutional Quality - Tran, Huong Thi Thanh; Nguyen, Bich Ngoc; Nguyen, Thao Thi Phuong; Cao, Quang Quoc (International Journal of Energy Economics and Policy, 2026)
This study uses a fixed-effects regression model with Robust standard errors, employing data from 52 countries between 2017 and 2022 to examine the impact of financial inclusion (FI) on CO2 emissions through the mediating role of renewable energy (RE) and institutional quality. The research results present a multifaceted picture of the impact of FI on CO2 emissions and the role of RE alongside institutional quality. The positive impact of FI on CO2 emissions suggests that the current expansion of access to finance primarily promotes production and consumption in a way that increases demand for traditional energy, thereby increasing emissions. The estimated indirect effects are all negative and statistically significant, implying that FI has the potential to reduce emissions through RE when supported by appropriate institutional frameworks. Current institutional frameworks are not strong enough to reduce emissions, but the interaction between RE and institutional quality could reverse this trend, helping to slow down the rate of CO₂ increase. Based on the results obtained, the study provides recommendations to policymakers and organizations to reduce CO₂ emissions in countries in the future.